Analisis Karakteristik Flashover Dan Arus Bocor Pada Isolator Porselin Yang Dipengaruhi Polutan Lumut Bryum SP. - Rajagukguk, Managam (Faculty of Engineering, Universitas Tanjungpura, 2011)
Abstract This research discussed the influence of a pollutant of bryum sp moss on the flashover voltage and leakage current characteristics of 254 mm x 146 mm ball and socket type of pin insulator, with creapage distance ( L ) of 31 cm and surface area (S) 0f 1500 mm2. The tests are conducted in High Voltage Engneering Laboratory, Tanjungpura University, Pontianak, by controlling relative humidity (RH) in a fog chamber at fixed internal values of 60 69 %, 70-79%,80-89% and 90-100%. The sample used are contaminated insulator at which bryum sp moss naturally had been grown on it surface. The results of research show that the existence of bryum sp. Accompanied by very humid condition resulted in decline of flashover voltage and in the contrary increase the leakage current . According to the obtained data, the flasover voltage under 80% of RH was not many declines compare to that of over 80% RH. It is considered that under 80% of bryum sp.seems to act as non conductive contaminant, and vice verse. Kata kunci : Insulator Suspension, flashover, leakage current, humidity, pollutant, moss.